Location and daily mobility - Øystein Engebretsen (European Regional Science Association (ERSA), 2005)
The aim of this paper is to discuss the interaction of location and daily mobility in cities. According to previous research the length of daily travel and the amount of car use in cities are influenced by urban density and residential location, thus focusing on urban sprawl as one of the main challenges for sustainable urban planning. However, during the last 10-15 years it has been more popular to settle in the inner city areas of Norwegian cities. This re-urbanisation has resulted in a stabilization of the urban density and a growth of the settlement in less car dependent areas. Nevertheless the car traffic is increasing. One reason for this may be the location of activities. Compared to the influence of urban density and residential location, the location of business and other activities seems to be an equally (or more) important causal factor for differences in daily mobility and increased car use. The paper presents analyses of travel behaviour in the cities of Oslo, Bergen, and Trondheim. The main focus is on how travel behaviour is affected by the location of homes (trip origin), the location of trip destinations, the accessibility with car and public transport, and the access to work place parking. The analysis is based on a database containing merged data from four large travel surveys conducted in 2001. In the travel surveys the origins and destinations are geocoded with reference to census units. This gives unbiased information about where the trips started and ended, and thus makes it possible to analyse the interaction of location and daily mobility. The analysis is carried out through using GIS based travel survey maps and other spatial analysing techniques. To some extent, the results support the planning philosophy underlying the Dutch ABC planning model that was introduced 15 years ago.
Keywords: 330